Elaboração e caracterização de filmes biodegradáveis de gelatina incorporados com argila bentonita ionicamente modificada - Garrido, Murillo Alves (Universidade Federal Rural do Semi-Árido, 2019)
Biofilms are biodegradable and / or edible films made from biopolymers, capable of forming a continuous matrix. The application of biofilms as packaging is directly related to its characteristics, and to the possible interactions of these with the product and the environment. There is evidence that proteins are promising materials because of the wide range of functional properties. Gelatine is an attractive biomaterial, due to its great production and low cost. However, gelatine has limitations in its physicochemical properties when compared to synthetic polymers. The improvement of these properties was proposed in this study from the incorporation of bentonite clay in the gelatin films. In order to increase the interaction between clay and gelatin, the clay was modified in the presence of surfactant (sodium dodecyl sulfate), aiming at the basal spacing between the silicate layers. The gelatine films with modified bentonite clay were characterized as bionanocomposite through Optical Microscopy (MO), Contact Angle (AC), water vapor permeability (PVA), solubility, mechanical properties and moisture content. Among them, it reduced the permeability to water vapor by 40.8% and increased the rupture stress by 55%. The films with the highest clay contents were the ones that contributed the most to the improvement of the physico chemical properties of the control gelatin film.
Monografia
Keywords: Filmes de bionanocompósitos; Bionanocomposit films; Gelatina; Gelatyn; Glicerol; Glycerol; Argila bentonita; Bentonite clay; Troca iônica; Ionic exchange; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA